2011
DOI: 10.1063/1.3580329
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ripple formation on different band-gap semiconductor surfaces using femtosecond pulses

Abstract: Nano-ripple formation from ultrashort laser pulse irradiation of semiconductors of different band gaps has been studied using a Ti-sapphire laser with 8 mJ energy, 45 fs pulse duration and 800 nm wavelength (1.5eV) at a fluence in the range of ∼100 mJ/cm2 −1J/cm2. The effects of the number of laser shots, angle of incidence, laser polarization, fluence, incident laser wavelength, bandgap, and ambient medium on the ripple period, have been studied. Depending upon the experimental parameters nano-ripple sizes va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Therefore, it appears clear the necessity to possess a handy model, which allows foreseeing directly LIPSS interspaces from key process parameters of the laser, such as, for instance, the laser fluence and number of pulses. It is well known that under irradiation of linear polarized femtosecond laser pulses, in a range of fluences determined by the material properties, grating structures with spatial periodicity slightly smaller than the laser wavelength are self-organized and oriented perpendicular to the laser polarization direction [4][5][6][7][8]. Nevertheless, the physical mechanisms at the base of LIPSS formation are still highly debated in literature and many models have been proposed [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it appears clear the necessity to possess a handy model, which allows foreseeing directly LIPSS interspaces from key process parameters of the laser, such as, for instance, the laser fluence and number of pulses. It is well known that under irradiation of linear polarized femtosecond laser pulses, in a range of fluences determined by the material properties, grating structures with spatial periodicity slightly smaller than the laser wavelength are self-organized and oriented perpendicular to the laser polarization direction [4][5][6][7][8]. Nevertheless, the physical mechanisms at the base of LIPSS formation are still highly debated in literature and many models have been proposed [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Figure Earlier works on LIPSS have suggested that the observed ripples could be resultant of interference of the incident electromagnetic wave and surface scattered electromagnetic wave. 36 Furthermore, liquid media plays a dominant role in the formation of ripple structures which was evident from FESEM images. Since the properties of liquid medium interacting with the metallic plasma plume is different, redistribution of metallic melt under the influence of recoil pressure (which depends on latent heat of vaporization) of liquid molecules was different.…”
mentioning
confidence: 95%
“…The irradiation of solids with multiple linear polarized femtosecond laser pulses at fluences close to the damage threshold leads to the formation of laser-induced periodic surface structures (LIPSS) on the surface of almost all materials [1][2][3][4]. For strong absorbing materials such as metals or semiconductors, in most cases low-spatial-frequency LIPSS (LSFL) are observed with a period Λ LSFL close to the irradiation wavelength λ [1,2,4].…”
Section: Introductionmentioning
confidence: 99%